Closed-Tube PCR with Nested Serial Invasion Probe Visualization Using Gold Nanoparticles. (6th January 2020) - Wang, Jianping; Zou, Bingjie; Ma, Yinjiao; Ma, Xueping; Sheng, Nan; Rui, Jianzhong; Shao, Yang; Zhou, Guohua
Abstract: BACKGROUND: Detecting DNA biomarkers related to personalized medicine could improve the outcome of drug therapy. However, personalized medicine in a resource-restrained hospital is very difficult because DNA biomarker detection should be performed by well-trained staff and requires expensive laboratory facilities. METHODS: We developed a gold nanoparticle–based "Tube-Lab" to enable DNA analysis in a closed tube. Gold nanoparticle–modified probes (GNPs) were used to construct an inexpensive and simple DNA sensor for signal readout. The method consists of 3 steps (template amplification, sequence identification, and GNP-based signal readout), bridged by an invasive reaction. With temperature control at each step, the 3 reactions proceed sequentially and automatically in a closed tube without any liquid transfer. We used Tube-Lab to detect different biomarkers in blood, tissue, and plasma, including US Food and Drug Administration–approved pharmacogenomic biomarkers (single nucleotide polymorphisms, somatic mutations). RESULTS: The combination of PCR-based template replication and invader-based signal amplification allowed detection of approximately 6 copies of input DNA and the selective pick up 0.1% mutants from large amounts of background DNA. This method highly discriminated polymorphisms and somatic mutations from clinical samples and allowed a "liquid biopsy" assay with the naked eye. CONCLUSIONS: Tube-Lab provides a promising and cost-effective approach for DNA biomarker analysis, including polymorphisms and somatic mutations from blood DNA, tissue DNA, or circulating tumor DNA in plasma, which are critical for personalized medicine.